Perancangan Reaktor Etilen Oksida (R-101) Pada Pabrik Etilen Oksida Dari Etilen Dan Oksigen Dengan Proses Dow Meteor Dengan Kapasitas Produksi 200.000 Ton/Tahun - Meysara Meysara; Bahruddin Bahruddin (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2021)
Ethylene oxide (C2H4O), also known as oxirane, is an organic compound in the ether group. Ethylene oxide is a colorless, sweet-smelling gas, flammable at room temperature and is a highly reactive compound. The purpose of designing this ethylene oxide reactor is to determine the type of reactor used and the dimensions of the reactor with an ethylene oxide production capacity of 200,000 tons / year. The reactor design methodology was carried out using Aspen Plus V10 software. Where from this application the data obtained from the ethylene oxide reactor volume (R-101) is 34.75 m3. In designing this reactor, a fixed bed multitube type reactor is used which functions to react ethylene and oxygen to ethylene oxide using a silver catalyst. With a capacity of 200,000 tons / year, the height of the reactor designed is 8.74 m, diameter 3.84 m, and the number of tubes is 1539 tubes.Keywords : Aspen Plus V10, Ethylene Oxide, Fixed Bed Multitube, Reactor